Abdominal wall tension increases using Dynamic Neuromuscular Stabilization principles in different postural positions. (December 2022) - Madle, Katerina; Svoboda, Petr; Stribrny, Martin; Novak, Jakub; Kolar, Pavel; Busch, Andrew; Kobesova, Alena; Bitnar, Petr
Abstract: Background: Intra-abdominal pressure (IAP) is an important mechanism stabilizing the spine and trunk. IAP regulation depends on the coordination of abdominal muscles, diaphragm and pelvic floor muscles. Objective: To determine the differences in abdominal wall tension (AWT) of various postural positions, first without any correction, then after verbal and manual instructions according to Dynamic Neuromuscular Stabilization (DNS) principles. Methods: In a cross-sectional observational study, thirty healthy individuals (mean age = 22.73 ± 1.91 years) were fitted with two Ohmbelt sensors contralaterally above the inguinal ligament and in the upper lumbar triangle. AWT was measured during five postural positions: sitting, supine with legs raised, squat, bear and hang position. First, spontaneous AWT was measured, then again after manual and verbal instructions following DNS principles. Results: AWT increased significantly with DNS instructions compared to spontaneous activation. Both sensors recorded significant increases ( p < .01; Cohen's d = −1.13 to −2.06) in all observed postural situations. The increase in activity occurred simultaneously on both sensors, with no significant differences noted in pressure increases between the sensors. The greatest activation for both sensors occurred in the bear position. Significant increases in activity were identified for both sensors in the supine leg raise position and in the bear position compared to spontaneous activation in sitting ( p < .001). There were no statistically significant differences (for both sensors) between women and men in any position. Conclusion: The amount of AWT significantly increases after verbal and manual instructions according to DNS. The greatest abdominal wall activation was achieved in the bear position. Highlights: Spontaneous AWT increases in supine leg raise and bear position vs. sitting. Instruction according to DNS increases AWT in all four postural positions tested. No differences in AWT were noted between gender or sensor location. The greatest AWT occurred in the bear position.